1998
DOI: 10.1002/(sici)1098-2795(199802)49:2<196::aid-mrd10>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tyrosine kinase inhibitor on the motility and ATP concentrations of fowl spermatozoa

Abstract: The possible role of tyrosine kinase in the regulation of fowl sperm motility was investigated by using a stable analogue of erbstatin, methyl 2,5‐dihydroxycinnamate (2,5‐MeC), a specific inhibitor of tyrosine kinase. This inhibited the motility of intact spermatozoa at 30°C in a dose‐dependent manner. In contrast, the motility of demembranated spermatozoa was not inhibited by the same concentrations of 2,5‐MeC. At 40°C, both intact and demembranated spermatozoa were almost immotile with or without 2,5‐MeC. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…(1998) had observed that PTK inhibitors 2,5‐MeC and poly glu‐tyr (4:1) had no effect on the motility of demembranated fowl spermatozoa but 2,5‐MeC inhibited motility of intact spermatozoa. Based on this observation Ashizawa et al . (1998) suggested that the tyrosine kinase activity which is associated with sustenance of sperm motility in fowl spermatozoa is not retained in the axoneme and/or accessory cytoskeletal components but may be present in the plasma membrane of spermatozoa.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…(1998) had observed that PTK inhibitors 2,5‐MeC and poly glu‐tyr (4:1) had no effect on the motility of demembranated fowl spermatozoa but 2,5‐MeC inhibited motility of intact spermatozoa. Based on this observation Ashizawa et al . (1998) suggested that the tyrosine kinase activity which is associated with sustenance of sperm motility in fowl spermatozoa is not retained in the axoneme and/or accessory cytoskeletal components but may be present in the plasma membrane of spermatozoa.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, if permeability was responsible then piceatannol which inhibited motility of intact spermatozoa should have also inhibited the motility of demembranated spermatozoa. In an earlier study Ashizawa et al . (1998) had observed that PTK inhibitors 2,5‐MeC and poly glu‐tyr (4:1) had no effect on the motility of demembranated fowl spermatozoa but 2,5‐MeC inhibited motility of intact spermatozoa.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, it may be that PKC involvement in sperm motility expression is species related, reflecting the ability of Ca 2ϩ to stimulate motility: the ion has no effect in boar sperm (Tajima et al, 1987; see also ''Materials and Methods''). There have also been reports that tyrosine phosphorylation plays a role in the control of motility (Vijayaraghavan et al, 1997;Ashizawa et al, 1998;Si and Okuno, 1999), although Ain et al (1999) found no effect of the PTK inhibitor tyrphostin A-47 on hamster sperm motility. In our experiments, sperm preincubated with the general PTK inhibitor lavendustin A (Onoda et al, 1989;O'Dell et al, 1991) showed no changes either in basal motility or in the initial degree to which bicarbonate was able to stimulate motility.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these events lead to an increase in the tyrosine phosphorylation of specific sperm proteins (Leclerc et al, 1996(Leclerc et al, , 1998Ficarro et al, 2003). An elevation in protein phosphotyrosine content has also been shown to be important in other sperm functions such as the acrosome reaction (Naz and Rajesh, 2004) and the hyperactivation, which is a motility pattern generally associated with sperm capacitation (Carrera et al, 1996;Leclerc et al, 1996;Ashizawa et al, 1998;Mahony and Gwathmey, 1999;Si and Okuno, 1999). Phosphorylation of the fibrous sheath components would cause a decrease in the stiffness of this flagellar sub-fraction, rendering it able to generate greater bends causing sperm hyperactivation (Si and Okuno, 1999).…”
Section: Introductionmentioning
confidence: 99%